Smoking history is negatively associated with allergen specific immunotherapy efficacy: a retrospective analysis - Romantowski, Jan (Postepy Dermatol Alergol, 2019)
INTRODUCTION: Allergen specific immunotherapy (AIT) is the only treatment modifying the course of the disease in patients allergic to airborne allergens. It has been proven to be effective in allergic populations, however individual patients vary in terms of response to the therapy. AIM: To assess the factors that might affect the efficacy of AIT. MATERIAL AND METHODS: Patients treated with AIT for grass pollen or house dust mites were included. The efficacy of AIT was assessed with the use of Allergy Control Score (ACS), performed before and at least 1 year after AIT. The following variables were assessed as potential risk factors for a worse response to AIT: age, gender, type of allergy, type of allergen, type of vaccine, type of AIT and smoking history. RESULTS: The study group consisted of 145 subjects.AIT was effective in the entire group; the mean ACS results decreased from 21.14 to 14.41 points (p< 0.0001). No differences in efficacy in terms of assessed risk factors were found, except for smoking history (ACS change in the smoking group was smaller: from 21.8 to 18.1 points; p = 0.09, OR = 0.323; 95% CI: 0.11–0.88; p = 0.02). CONCLUSIONS: Smoking history may affect AIT outcomes.